Symbolism of the Ideology of Javanese Knights Based on the Iconography of the Visual Form of Punakawan in Javanese Wayang Purwa - Budi, Setyo; Susilo, Joko (Harmonia: Journal of Arts Research and Education, 2025)
Wayang purwa is a product of Javanese culture which constructs a world of symbols. The depiction of wayang figures does not represent human figures but the symbolisation of human characters and qualities. The research goal is to reveal hidden messages of the four punakawan wayang: Sêmar, Garèng, Pétruk, and Bagong, who are loyal followers of Arjuna in Javanese wayang purwa. Javanese puppets are indeed sourced from Mahabharata, but the four figures are additional figures from the creators. The research method is explorative qualitative and based on iconographical theory. The results of the study show that Sêmar symbolises ‘spirituality’, a Javanese knight must have a high level of spirituality; Garèng symbolises ‘personal awareness’, a knight must have awareness as an imperfect being; Pétruk symbolises a ‘visionary’, a knight must be able to look far into the future, and Bagong symbolise ‘holistic awareness’, a knight must also have empathy for his surroundings. Wayang should be understood as a world of symbols, but positioning the iconography of wayang from a representation of a human figure to the symbolisation of ‘character and aptitude’ is an ‘extreme interpretation’ within the boundaries of an interpretative study. This is a way of understanding Javanese culture in a cosmological context; what appears is not real because what is essential is invisible.